Emerging Research in Computing, Information, Communication and Applications ERCICA 2018, Volume 2 - Shetty, N. R.; Patnaik, L. M.; Nagaraj, H. C.; Hamsavath, Prasad Naik; Nalini, N. (Advances in Intelligent Systems and Computing,, 2019)
This book presents selected papers from the International Conference on Emerging Research in Computing, Information, Communication and Applications, ERCICA 2018. The conference provided an interdisciplinary forum for researchers, professional engineers and scientists, educators, and technologists to discuss, debate and promote research and technology in the emerging areas of computing, information, communication and their applications. The book discusses these research areas, providing a valuable resource for researchers and practicing engineers alike.